THE ROLE OF TOURISM DEVELOPMENT IN IMPROVING THE ECONOMIC WELFARE OF LOCAL COMMUNITIES (CASE STUDY OF SEMBALUN VILLAGE, SEMBALUN DISTRICT, EAST LOMBOK REGENCY) - Nazar Fajri, Lalu Moh.; Yaqutunnafis, Lale (Politea : Jurnal Politik Islam, 2025)
This study examines the development of community-based tourism in Sembalun Village, East Lombok Regency, as a strategic effort to improve the economic welfare of the community through participatory governance. Using a qualitative approach, data was collected through in-depth interviews, direct observations, and documentation of residents, tourism managers, and village officials. The results of the study show that tourism development in Sembalun contributes significantly to job creation, income diversification, and strengthening local cultural identity. However, there are still various challenges, such as limited infrastructure, low human resource capacity, and inequality in access to tourism benefits. This study also found that there are local initiatives that support inclusive participation, including through the role of youth groups, Pokdarwis, and BUMDes. These findings underscore the importance of local institutional empowerment, multi-stakeholder collaboration, and adaptive capacity building in the face of social and environmental risks. The study concludes that community-based tourism in Sembalun is a promising model for sustainable and inclusive rural development, if supported by consistent policies and fair governance